Excretory system learning in senior high school: comparative analysis of students’ problem solving skills - Maharani Aji Kharisma Rindah; Sri Dwiastuti; Yudi Rinanto (Biosfer: Jurnal Pendidikan Biologi, 2019)
Problem-solving skills are the skills essential for students to have. This research aimed to analyze the problem-solving skills of senior high school students in biology learning of excretory system topics. The method used was descriptive-quantitative. The data were collected using a problem-solving essay test. The subjects were the eleventh-grade students of senior high schools in Surakarta, who were divided into A category (upper class) and B category (low level). Based on the analysis result, it can be seen that the problem-solving skill achievement of the eleventh grade of A group includes: defining the problem (50.78%), examining the problem (40.62%), planning a solution (19.53%), implementing the solution (37.50%), and evaluating (40.62%); while that of B category includes: Defining the problem (46.35%), examining the issue (34.67%), planning a solution (18.54%), implementing the solution (20.96%), and evaluating (32.25%). The lowest percentage in both categories was found in planning the solution and evaluating. Based on the result, the average problem-solving skills in A group is 37.81% and B Category 32,26%. Based on the data, it can be concluded that students' problem-solving skills in A and B categories are still low. The skills can be improved by conducting problem-solving based learning and familiarizing students to solve problems according to problem-solving stages.